Theoretical models in psychoanalytic psychosomatic: A review - Galdi, Maíra Bittar [UNESP]; Campos, Érico Bruno Viana [UNESP] (Associacao Brasileira de Psicologia, 2017)
This article is a theoretical study of the psychoanalytic literature on the subject of psychosomatic that aims to review the approach models this phenomenon seeking to understand their differences and similarities in terms of theoretical basis. The results point to two different ways of looking at psychosomatic illnesses. In the French side, linked more or less directly to the Lacan perspective, the main references were Jacques-Alain Miller and Pierre Marty, the phenomenon is not a representational shift, but a failure in symbolization processes. In a second aspect, which brings together from the Psychosomatic School of Chicago to French authors not Lacanian, the main references were Joyce McDougall and Christophe Dejours, the psychosomatic phenomenon is understood in a divergent line, relating the formation of the symptom the unconscious confl icts. They are symbolized in the disease, but in a more precarious form of symbolization from the model of hysteria. Despite the differences, it is understood that no compromise on the principles towards the treatment, which is to defi ne a meaning for the symptom, not by the rescue of an unconscious fantasy as in the classic model of hysteria, but building a sense where there was no historical narrative thread.
Keywords: Psychoanalysis; Psychosomatic; Somatization; Symbolization